2011
DOI: 10.1186/1472-6920-11-52
|View full text |Cite
|
Sign up to set email alerts
|

Empathy in senior year and first year medical students: a cross-sectional study

Abstract: BackgroundThe importance of fostering the development of empathy in undergraduate students is continuously emphasized in international recommendations for medical education. Paradoxically, some studies in the North-American context using self-reported measures have found that empathy declines during undergraduate medical training. Empathy is also known to be gender dependent- (highest for female medical students) and related to specialty preference - (higher in patient-oriented than technology-oriented special… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
174
6
21

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(227 citation statements)
references
References 24 publications
26
174
6
21
Order By: Relevance
“…There is a need to further explore why most Asian students have almost similar scores but lower than the American studies. 8,20,21 The empathy scores at the entry point of medical school is much less than those found in US by Chen et al (115.5), Hojat et al (114.5) but similar to that from Iran (110.3). 8,11,14 The curriculum in this college is different in many respects from medical schools in US, Japan and Iran.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…There is a need to further explore why most Asian students have almost similar scores but lower than the American studies. 8,20,21 The empathy scores at the entry point of medical school is much less than those found in US by Chen et al (115.5), Hojat et al (114.5) but similar to that from Iran (110.3). 8,11,14 The curriculum in this college is different in many respects from medical schools in US, Japan and Iran.…”
Section: Discussionmentioning
confidence: 68%
“…In this study there is significant difference (p ¼ 0.012) in empathy scores between male and female with later scoring more than male students (mean female students 106.5v/s male students 101.89, Standard deviation 19.901 & 16.164 respectively) (Table 4), which is in consonance with studies from US Portugal and Japan. 8,13,20 However the study from Iran did not find any significant difference though female students did have mean higher scores (105.6vs103.7). 23 The difference in this study from Iran could be due to varied proportion of female students to male students in both studies (22.13% vs70.16%).…”
Section: Discussionmentioning
confidence: 81%
“…in Japan, Korea [18,23] and Portugal [24] have shown an increase in empathy. Winseman, Malik, Morison, and Balkoski [25] reported that both personal and educational factors influence medical students' empathy in the course of their studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that beside the decline of student empathy during their medical school years (Hojat et al, 2004;Chen et al, 2012;Shariat and Habibi 2013), greater levels of empathy has been also demonstrated in medical students in their final years (Kataoka et al, 2009;Roh et al, 2010;Magalhães et al, 2011). So, there is a need to study changes in student empathy during medical education and find out the reasons that affect the medical students' visions of the importance of human interactions and empathy in patient encounters.…”
Section: Discussionmentioning
confidence: 99%
“…Unsuitable learning environments, cynicism/loss of idealism (Hojat et al, 2004;Newton et al, 2008), distress (Neumann et al, 2011), hidden curriculum (Eikeland et al, 2014), negative role-models, a high volume of materials to learn, time pressure, patient factors and overreliance on computer-based diagnostic and therapeutic technology can affect the students and cause a decline in empathy. However, in one longitudinal study (Quince et al, 2011), no significant change was observed, and in some cross-sectional studies greater levels of empathy were observed in medical students in their final year (Kataoka et al, 2009;Roh et al, 2010;Magalhães et al, 2011).…”
Section: Introductionmentioning
confidence: 99%